Apport de l’analyse sémantique dans la recherche sur les prédicats de communication: du sens d’un prédicat au texte et à la traduction - Pozierak-Trybisz, Izabela (Neophilologica, 2010)
This study aims to present a semantic analysis of a verbal communication: senses of predicates, propositional constructions, structures topic-focus of texts built around predicates of communication to find out ‘strategy’ for the transmission of information in such texts. The practicale use of it is translation. Analyze are based based on the methodology of the grammar-based semantic of S. Karolak.